2019
DOI: 10.1158/1055-9965.epi-18-0452
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Colonoscopy Following Diagnosis of Advanced Adenomas: An Analysis within Integrated Healthcare Delivery Systems

Abstract: Background: To reduce colorectal cancer incidence and mortality, experts recommend surveillance colonoscopy 3 years after advanced adenoma removal. Little is known about adherence to that interval. Methods: We describe patterns of and factors associated with subsequent colonoscopy among persons with ≥3 adenomas and/or ≥1 adenoma with villous/tubulovillous histology in four US integrated healthcare delivery systems. We report Kaplan-Meier estimators of the cumulative percentage of patients undergoing colonosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…The high rates of colonoscopy follow-up after a positive FIT result are consistent with previous reports of FITpositive follow-up in this organized programmatic screening setting 21 and are higher than those reported in other settings, [22][23][24] including a safety-net hospital system catering to the underserved. 23 The high rates of follow-up were achieved through an organized screening program that included prompt communication of positive results to patients and their physicians, colonoscopy capacity and preferential triage of patients with a positive FIT result, active outreach to patients to promptly schedule colonoscopy after a positive FIT result, and centralized tracking of and follow-up for examination completion.…”
Section: Discussionsupporting
confidence: 89%
“…The high rates of colonoscopy follow-up after a positive FIT result are consistent with previous reports of FITpositive follow-up in this organized programmatic screening setting 21 and are higher than those reported in other settings, [22][23][24] including a safety-net hospital system catering to the underserved. 23 The high rates of follow-up were achieved through an organized screening program that included prompt communication of positive results to patients and their physicians, colonoscopy capacity and preferential triage of patients with a positive FIT result, active outreach to patients to promptly schedule colonoscopy after a positive FIT result, and centralized tracking of and follow-up for examination completion.…”
Section: Discussionsupporting
confidence: 89%
“…11 As a significant proportion of patients with high-risk adenomas will either not undergo any surveillance or undergo surveillance later than guidelines recommend, the importance of complete adenoma resection should be given similar attention as achieving a high ADR. [54][55][56] Furthermore, recent revisions to colonoscopy surveillance guidelines include longer surveillance intervals than previously recommended; once these new surveillance intervals are implemented, complete adenoma resection will become even more important. 54,[57][58][59][60] Quality improvement initiatives have had great success in recent years in improving colonoscopy quality with regard to cecal intubation rates and ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study exploring surveillance patterns in community practice, Schoen et al found low rates of surveillance uptake at 3 years for patients diagnosed with an aTA (30.7%) or ≥ 3 non-advanced adenomas (19.5%) 8 . Across several large integrated health systems, Chubak et al reported similarly low uptake at 3 years for patients diagnosed with ≥ 3 adenomas and/or ≥ 1adenoma with villous/tubulovillous histology (10.2–30.9%) 9 . Akin to our findings, both studies noted a sudden rise in surveillance uptake in the immediate wake of the surveillance due date, and subsequent studies have shown increases in surveillance colonoscopy up to 6 years after HRA diagnosis, well after the recommended 3-year interval 8 , 11 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective cohort within community practice, only 30.7% of patients diagnosed with advanced tubular adenoma (aTA; defined by having at least one TA ≥ 1 cm, TA with tubulovillous/villous histology, or TA with high-grade dysplasia) and 19.5% of patients with 3 or more non-advanced adenomas completed surveillance by 3 years 8 . In a multisite cohort spanning 4 regional health systems, surveillance uptake at 3.5 years in patients with either 3 or more adenomas and/or 1 or more adenomas with tubulovillous/villous histology ranged between 18.3 and 59.5% 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation